Transformasi Spiritual Remaja: Studi Tentang Proses Tobat Dan Perubahan Perilaku Dalam Perspektif Psikologi Agama - Fajarnurrahmathadi; Liamufliha; Nazwaaulia; Nendrawijaya; Robbiatuladdawiyah; NoorAzidabatubara (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Spiritual transformation in adolescence is a significant psychological and religious phenomenon, particularly in the context of repentance processes and behavioral change. Adolescence is characterized by identity exploration, emotional turbulence, and vulnerability to moral and value conflicts. This article aims to examine the process of repentance among adolescents as a form of spiritual transformation and its implications for behavioral change from the perspective of the psychology of religion. The study employs a literature review method by analyzing theories of the psychology of religion, developmental psychology, and relevant religious studies. The findings indicate that the process of repentance in adolescents involves self-awareness, moral remorse, religious commitment, and the support of social and spiritual environments. Successful spiritual transformation contributes to positive behavioral changes, including increased self-control, moral maturity, and psychological well-being. This article is expected to serve as a reference for educators, counselors, and religious practitioners in assisting adolescents during their spiritual transformation phase.